2021
DOI: 10.1111/avsc.12584
|View full text |Cite
|
Sign up to set email alerts
|

Lichen communities on Populus tremula are affected by the density of Picea abies

Abstract: Questions Aspen (Populus tremula) is declining in the old‐growth forests of boreal Fennoscandia. This threatens the numerous taxa that are dependent on old aspens, including many epiphytic lichens. Potential methods to aid epiphytic lichens on aspen are centered around treatments which affect the density of Norway spruce (Picea abies). In this study, we investigated how epiphytic lichen communities on aspen are affected by the variation of spruce density in the immediate vicinity of the focal aspen. Location S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Long-term changes in canopy cover have been only scarcely studied, but it has been shown to have increased between 1959 and 2011 in unmanaged landscapes in northern Finland (Kulha et al 2020). Studies have shown that lichen richness is lower in dense stands with low light availability (Marmor et al 2012;Klein et al 2020;Nirhamo et al 2021). According to our results, over 80% of red-listed epiphytic lichens prefer high or intermediate light availability.…”
Section: Microclimatesupporting
confidence: 51%
See 1 more Smart Citation
“…Long-term changes in canopy cover have been only scarcely studied, but it has been shown to have increased between 1959 and 2011 in unmanaged landscapes in northern Finland (Kulha et al 2020). Studies have shown that lichen richness is lower in dense stands with low light availability (Marmor et al 2012;Klein et al 2020;Nirhamo et al 2021). According to our results, over 80% of red-listed epiphytic lichens prefer high or intermediate light availability.…”
Section: Microclimatesupporting
confidence: 51%
“…Our data suggests that some species prefer an unusual combination of high humidity and high light availability (see also Nilsson et al 2022). Our results highlight that dense forests are inhospitable to many red-listed lichens (see also Gauslaa et al 2006;Gauslaa et al 2007;Klein et al 2020;Nirhamo et al 2021). Instead, they require a sufficient availability of light, often in combination with relatively high humidity.…”
Section: Microclimatementioning
confidence: 54%